High-strength, high-plasticity and high-hardness Al-Mg alloy and preparation method thereof
By using specific component ratios and laser additive manufacturing processes, high-strength, high-ductility, and high-hardness Al-Mg alloys were prepared, solving the problems of insufficient strength and high cost in existing technologies and realizing the industrial production of high-performance alloys.
Patent Information
- Application Number
- CN202511158719.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-08-19
AI Technical Summary
The existing 5xxx series Al-Mg alloys have insufficient absolute strength and cannot be strengthened by heat treatment in high-performance applications such as aerospace, which limits their application in these fields. At the same time, the addition of precious metal elements increases production costs and reduces the plasticity of the alloy.
Al-Mg alloys with specific component ratios are used to prepare metal powders by high-pressure nitrogen atomization, and then laser additive manufacturing is carried out under the protection of high-purity argon to form nanoscale strengthening phases and bimodal structures, avoiding complex deformation processes and high-temperature heat treatment.
It achieves simultaneous improvement in high strength, plasticity and hardness, with an alloy density of 99.7%, tensile strength ≥475MPa, yield strength ≥411MPa, and elongation ≥16%, avoiding cracking and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of high-performance alloy materials, in particular to a high-strength and high-plasticity Al-Mg alloy and a preparation method thereof. BACKGROUND
[0002] The 5xxx series Al-Mg alloy has low density, high specific strength, excellent electrical conductivity and thermal conductivity, and good corrosion resistance, and its application proportion in the fields of transportation, building structure, medical equipment and the like is increasing; however, for high-performance application fields such as aerospace, the absolute strength is relatively insufficient and the alloy cannot be heat-treated for strengthening (heat treatment is not suitable for improving the strength of the alloy), thus limiting the wide application of the alloy in the fields of aerospace and the like.
[0003] The existing research approaches to solve the above problems mainly include: using complex plastic deformation processes such as forging and extrusion or adding a large amount of Ti, V and other noble metal elements. However, these methods significantly increase the production cost. Moreover, although the high-cost alloy elements make the alloy heat-treatable for strengthening or the complex process can improve the strength of the alloy, the plasticity of the alloy is often reduced, resulting in difficulty in simultaneously improving the strength and plasticity of the alloy. In addition, the complex deformation process will also cause the hardness of the alloy to decrease and induce cracking. For example, the Al-8.8Fe-2V-7.3Si alloy prepared by Yaneva et al. through a rapid solidification process and a hot extrusion process has a yield strength of 404.1 MPa, but the elongation is only 2%. Therefore, how to reduce the content of noble metal elements, reduce the cost, simplify the process, and obtain an Al-Mg alloy with simultaneous improvement of strength and plasticity is a technical problem to be solved at present. SUMMARY
[0004] In order to solve the above technical problems, the present application provides a high-strength and high-plasticity Al-Mg alloy, which comprises, by mass percentage: Mg: 5-15%, Mn: 0.4-2.3%, Sc: 0.4-1.5%, Zr: 0.2-1.5%, Si: 0.2-1%, Fe: 0.04-0.2%, and the balance of Al and unavoidable impurities, wherein the content of the impurities is ≤0.02%. The preparation method thereof comprises the following steps:
[0005] (1) melt commercial pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si and Al-20Fe according to the ratio at 680-800℃, then cool to 600-750℃, add commercial pure magnesium until completely melted, stir for 10-60min to obtain an alloy melt;
[0006] (2) the alloy melt obtained in step (1) is broken by a high-pressure nitrogen gas atomizer, solidified to form a metal powder, and after screening, an Al-Mg alloy powder is obtained, wherein the particle size of the Al-Mg alloy powder is 5-80 μm;
[0007] (3) the Al-Mg alloy powder obtained in step (2) is dried at 80-120°C for 3-8h in vacuum, and then an Al-Mg alloy forming piece is obtained by laser additive manufacturing treatment of 50-600 layers under high-purity argon protection, wherein the laser additive manufacturing treatment is as follows: the laser scanning is in strip mode, and each layer of laser additive manufacturing treatment needs to be subjected to twice laser scanning melting treatment, and each laser scanning melting treatment is as follows: the laser power is 150-420 W, the scanning speed is 600-2000 mm / s, the powder layer laying thickness is 20-50 μm, and the laser scanning interval is 100-130 μm; compared with the upper layer of laser additive manufacturing treatment, the scanning path of the lower layer of laser additive manufacturing treatment is deflected counterclockwise by 50-90°, and additive manufacturing treatment is carried out according to the process of the upper layer; the Al-Mg alloy forming piece has a density ≥ 99.7%, a tensile strength σ b ≥ 475 MPa, a yield strength σ 0.2 ≥ 411 MPa, and an elongation ≥ 16%;
[0008] (4) the Al-Mg alloy forming piece obtained in step (3) is heat treated at 300-400°C for 2-12h to obtain a high-strength and high-plasticity Al-Mg alloy; the high-strength and high-plasticity Al-Mg alloy has high-density nanoscale Al6(Mn, Fe) with a diameter ≤ 147 nm, Mg2Si with a diameter ≤ 131 nm, and ultra-fine nanoscale Al3(Sc, Zr) strengthening phase with a diameter ≤ 4 nm, and a bimodal structure of alternating coarse and fine crystals is obtained, and the fine crystal accounts for the majority, with a fine crystal area ratio ≥ 55.7%, a fine crystal average diameter ≤ 558 nm, and a coarse crystal average diameter ≤ 2.6 μm; the Al3(Sc, Zr) strengthening phase is of L12 type, and the number density is ≥ 7.2×10 23 m -3 ; the high-strength and high-plasticity Al-Mg alloy has a tensile strength σ b ≥ 598 MPa, a yield strength σ 0.2 ≥ 584 MPa, an elongation ≥ 11.2%, and a Vickers hardness ≥ 180 HV.
[0009] Further, the particle size of the Al-Mg alloy powder in step (2) is 15-53 μm.
[0010] Further, the aluminum alloy plate in step (3) is one of 5A06 or AA5083.
[0011] Further, the step (3) is performed under the protection of high-purity argon.
[0012] Further, the step (3) is performed under the protection of high-purity argon.
[0013] Compared with the prior art, the application significantly reduces the alloy addition cost, simplifies the process, realizes the short process and industrialized production through the synergistic regulation of component interaction, component ratio, process and process parameters without adding a large amount of noble metal and adopting complex processes such as large deformation, and has the beneficial effects as follows:
[0014] 1. Compared with the prior art, the Al-Mg series alloy forming part obtained after additive manufacturing has a density ≥ 99.7%, a tensile strength σ b ≥ 475 MPa, a yield strength σ 0.2 ≥ 411 MPa, and an elongation EL ≥ 16%.
[0015] 2. Although the existing forging and extrusion processes can realize grain refinement, the refinement degree is micron level and it is difficult to achieve nanometer scale; or high-density dislocations are introduced to achieve the purpose of improving strength, but high-density dislocations will reduce plasticity, for example: the Al-6Zn-3Mg-Cu alloy obtained by the prior art through plasma sintering, hot forging, hot extrusion and T6 treatment has an average grain size of 2.66 μm, a MgZn2 strengthening phase size of ~ 1 μm, and an elongation of ~ 8%. The application can realize nanometer-level grain refinement, nanometer-level second phase refinement and improved solid solution strengthening effect at the same time, simultaneously improve the strength, plasticity and hardness of the alloy, and avoid cracking; at the same time, a bimodal structure with alternating coarse and fine crystals (mainly fine crystals, with an average diameter of the fine crystals ≤ 558 nm, an average diameter of the coarse crystals ≤ 2.6 μm, and a fine crystal area ratio ≥ 55.7%) is obtained, and the solid solution strengthening effect of Mg element in the Al matrix is greatly improved (the solid solution of Mg element in the Al matrix obtained by the traditional process is generally ≤ 1.4 wt.%, and the solid solution of Mg element in the Al matrix obtained by the application is ≥ 5.8 wt.%), and at the same time, high-density refined Al6(Mn, Fe) (diameter ≤ 147 nm), Mg2Si (diameter ≤ 131 nm) and Al3(Sc, Zr) (diameter ≤ 4 nm) nanometer-level strengthening phases are formed, wherein the ultra-fine nanometer Al3(Sc, Zr) strengthening phase is L12 type, the number density is ≥ 7.2 × 10 23 m -3 , the final Al-Mg series alloy has a tensile strength σ b ≥ 598 MPa, a yield strength σ 0.2≥ 584 MPa, elongation EL ≥ 11.2%, Vickers hardness ≥ 180 HV. DETAILED DESCRIPTION
[0016] In order to make the objectives, technical solutions and effects of the present application clearer and more apparent, the present application will be described in detail below in conjunction with specific examples. The examples are only preferred embodiments of the present application, and are not a limitation of the present application. Based on the examples in the present application, all other examples obtained by those of ordinary skill in the art without making any creative efforts, are within the scope of protection of the present application.
[0017] Example 1
[0018] A high-strength and high-plasticity, high-hardness Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy (Mg: 6.8%, Mn: 0.53%, Sc: 0.72%, Zr: 0.57%, Si: 0.36%, Fe: 0.055%, the rest being Al and unavoidable impurities, the impurities being ≤0.02%, in terms of mass percentage), a preparation method thereof comprising the following steps:
[0019] (1) Commercially pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si and Al-20Fe are melted at 800°C in a mass percentage ratio, then cooled to 730°C, and commercial pure magnesium is added until completely melted, and the alloy melt is obtained after stirring for 60 min;
[0020] (2) The alloy melt obtained in step (1) is broken up by a high-pressure nitrogen gas atomizer and solidified to form a metal powder, and the Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy powder with a particle size of 15-53 μm is obtained after screening;
[0021] (3) After the Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy powder obtained in step (2) is vacuum dried at 80-120°C for 3h, an Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece is obtained after laser additive manufacturing treatment of 333 layers under high-purity argon protection, using a 5A06 aluminum alloy plate as a substrate, the laser additive manufacturing treatment being: laser scanning in strip mode, two laser scanning and melting treatments are required for each layer of powder laser additive manufacturing, each laser scanning and melting treatment being: laser power of 180W, scanning speed of 1300mm / s, powder layer laying thickness of 30μm, and laser scanning spacing of 100μm; compared with the upper layer laser additive manufacturing treatment, the scanning path of the lower layer laser additive manufacturing treatment is deflected counterclockwise by 67°, and additive manufacturing treatment is carried out according to the process of the upper layer; the density of the Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece after additive manufacturing is 99.7%, the tensile strength σ b is 475MPa, the yield strength σ 0.2 is 415MPa, and the elongation is 16%;
[0022] (4) After the Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece obtained in step (3) is heat treated at 325°C for 2.5h, a high-strength and high-plasticity Al-6.8Mg-0.53Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy with a bimodal structure of alternating coarse and fine crystals is obtained, and the fine crystals are mainly present, with a fine crystal area ratio of 59.7%, a fine crystal average diameter of 486nm, a coarse crystal average diameter of 2.6μm, and high-density refined Al6(Mn,Fe) (diameter of 147nm), Mg2Si (diameter of 131nm) and Al3(Sc,Zr) (diameter of 4nm) nanoscale strengthening phases being formed, wherein the ultra-fine nanoscale Al3(Sc,Zr) strengthening phase is of L12 type, and the number density is 7.2×10 23 m -3 ; the tensile strength σ b of the alloy is 600MPa, the yield strength σ 0.2 is 584MPa, the elongation is 12.2%, and the Vickers hardness is 180HV.
[0023] Example 2
[0024] High strength-to-plasticity ratio and high hardness Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy (Mg: 8%, Mn: 0.57%, Sc: 0.72%, Zr: 0.57%, Si: 0.36%, Fe: 0.055% by mass, with the balance being Al and unavoidable impurities, the impurities being ≤0.02%) and a preparation method thereof, the method comprising the following steps:
[0025] (1) Commercially pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si, and Al-20Fe are melted at 780°C in a mass ratio, then cooled to 720°C, and commercially pure magnesium is added until completely melted, and the alloy melt is obtained after stirring for 55 min;
[0026] (2) The alloy melt obtained in step (1) is broken up by a high-pressure nitrogen gas atomizer and solidified to form a metal powder, and the Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy powder with a particle size of 15-53 μm is obtained after screening;
[0027] (3) The Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy powder obtained in step (2) is vacuum dried at 80-120°C for 5 h, and then an Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece is obtained by 333-layer laser additive manufacturing under high-purity argon protection using a 5A06 aluminum alloy plate as a substrate, wherein the laser additive manufacturing is performed in a strip mode, and each layer of powder requires two laser scanning and melting processes, each laser scanning and melting process is performed at a laser power of 240 W, a scanning speed of 1700 mm / s, a powder layer deposition thickness of 40 μm, and a laser scanning interval of 100 μm; compared with the upper layer additive manufacturing, the scanning path of the lower layer additive manufacturing is deflected counterclockwise by 67°, and the additive manufacturing is performed according to the process of the upper layer; the density of the Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece after additive manufacturing is 99.8%, the tensile strength σ b is 477 MPa, the yield strength σ 0.2 is 411 MPa, and the elongation is 16.5%;
[0028] (4) the Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy formed piece obtained in step (3) is kept at 325℃ for 2h to obtain a high strength and plasticity and high hardness Al-8Mg-0.57Mn-0.72Sc-0.57Zr-0.36Si-0.055Fe alloy, which has a bimodal structure of coarse and fine crystal alternately arranged, and mainly in fine crystal, the area percentage of fine crystal is 55.7%, the average diameter of fine crystal is 558nm, the average diameter of coarse crystal is 2.5μm, and high density refined Al6(Mn,Fe) (diameter of 145nm), Mg2Si (diameter of 128nm) and Al3(Sc,Zr) (diameter of 3.9nm) nanoscale strengthening phases are formed, wherein the ultrafine nanoscale Al3(Sc,Zr) strengthening phase is L12 type, and the number density is 7.22×1013 / m2. 23 m -3 ; the tensile strength σ b of the alloy is 604MPa, the yield strength σ 0.2 is 590MPa, the elongation is 11.5%, and the Vickers hardness is 180.9HV.
[0029] Example 3
[0030] A high strength and plasticity and high hardness Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy (Mg: 6%, Mn: 0.53%, Sc: 0.75%, Zr: 0.57%, Si: 0.36%, Fe: 0.055% by mass, the balance being Al and unavoidable impurities, and the impurities ≤0.02%), and a preparation method thereof, which comprises the following steps:
[0031] (1) commercially pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si and Al-20Fe are melted at 785℃ according to the ratio by mass, then cooled to 710℃, and commercially pure magnesium is added to complete melting, and the alloy melt is obtained after stirring for 58min;
[0032] (2) the alloy melt obtained in step (1) is broken by a high-pressure nitrogen gas atomizer and solidified to form a metal powder, and the Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy powder with a particle size of 15-53μm is obtained after screening;
[0033] (3) After the Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy powder obtained in step (2) is vacuum dried at 80-120°C for 4h, an Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece is obtained after laser additive manufacturing treatment of 333 layers under high-purity argon protection using a 5A06 aluminum alloy plate as a substrate, wherein the laser additive manufacturing treatment is: laser scanning in strip mode, two laser scanning and melting treatments are required for each layer of powder laser additive manufacturing, and each laser scanning and melting treatment is: laser power is 280W, scanning speed is 600mm / s, powder layer laying thickness is 30μm, and laser scanning spacing is 130μm; compared with the upper layer laser additive manufacturing treatment, the scanning path of the lower layer laser additive manufacturing treatment is deflected counterclockwise by 67°, and additive manufacturing treatment is carried out according to the process of the upper layer; the density of the Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece after additive manufacturing is 99.7%, the tensile strength σ b is 483MPa, the yield strength σ 0.2 is 439MPa, and the elongation is 18%;
[0034] (4) After the Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece obtained in step (3) is heat treated at 325°C for 3h, a high-strength and high-plasticity and high-hardness Al-6Mg-0.53Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy is obtained, which has a bimodal structure with alternating coarse and fine crystals, and the fine crystals are mainly present, with a fine crystal area ratio of 58.2%, a fine crystal average diameter of 532nm, a coarse crystal average diameter of 2.55μm, and high-density refined Al6(Mn,Fe) (diameter of 140nm), Mg2Si (diameter of 125nm) and Al3(Sc,Zr) (diameter of 4nm) nanoscale strengthening phases are formed, wherein the ultra-fine nanoscale Al3(Sc,Zr) strengthening phase is of L12 type, and the number density is 7.23×10 23 m -3 ; the tensile strength σ b of the alloy is 598MPa, the yield strength σ 0.2 is 584MPa, the elongation is 11.4%, and the Vickers hardness is 180HV.
[0035] Example 4
[0036] High strength-to-plasticity ratio and high hardness Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy (Mg: 10%, Mn: 0.6%, Sc: 0.75%, Zr: 0.57%, Si: 0.36%, Fe: 0.055% by mass, with the balance being Al and unavoidable impurities, the impurities being ≤0.02%) and a preparation method thereof, the method comprising the following steps:
[0037] (1) Commercially pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si, and Al-20Fe are melted at 790°C in a mass ratio, then cooled to 725°C, and commercially pure magnesium is added until completely melted, and the alloy melt is obtained after stirring for 60 min;
[0038] (2) The alloy melt obtained in step (1) is broken up by a high-pressure nitrogen gas atomizer and solidified to form a metal powder, and the Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy powder with a particle size of 15-53 μm is obtained after screening;
[0039] (3) The Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy powder obtained in step (2) is vacuum dried at 80-120°C for 5 h, and then an Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece is obtained by 333-layer laser additive manufacturing under high-purity argon protection using a 5A06 aluminum alloy plate as a substrate, wherein the laser additive manufacturing is performed in a strip mode, and each layer of powder requires two laser scanning and melting processes, each laser scanning and melting process is performed at a laser power of 420 W, a scanning speed of 2000 mm / s, a powder layer deposition thickness of 40 μm, and a laser scanning interval of 130 μm; compared with the upper layer additive manufacturing, the scanning path of the lower layer additive manufacturing is deflected counterclockwise by 67°, and the additive manufacturing is performed according to the process of the upper layer; the density of the Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy shaped piece after additive manufacturing is 99.8%, the tensile strength σ b is 496 MPa, the yield strength σ 0.2 is 440 MPa, and the elongation is 18%;
[0040] (4) The Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy formed part obtained in step (3) is kept at 325℃ for 2h to obtain an Al-10Mg-0.6Mn-0.75Sc-0.57Zr-0.36Si-0.055Fe alloy with high strength, plasticity and hardness. The alloy has a bimodal structure with alternating coarse and fine crystals, and the fine crystals are dominant, with a fine crystal area ratio of 59.5%, a fine crystal average diameter of 496nm, and a coarse crystal average diameter of 2.4μm. High-density refined Al6(Mn,Fe)(diameter 133nm), Mg2Si(diameter 121nm) and Al3(Sc,Zr)(diameter 3.8nm) nanoscale strengthening phases are formed, among which the ultra-fine nanoscale Al3(Sc,Zr) strengthening phase is L12 type, with a number density of 7.28×10 23 m -3 ; the alloy tensile strength σ b is 609MPa, the yield strength σ 0.2 is 594MPa, the elongation is 11.2%, and the Vickers hardness is 181.5HV.
[0041] Comparative Example 1
[0042] Journal name: Powder Metallurgy Industry, year: 2025, paper author: Zhang Kang, Shi Zimu, Wang Xingfu, Liang Qihua, Han Fusheng, title: Effect of TiB2 on the microstructure and mechanical properties of Al-6Zn-3Mg-Cu aluminum alloy. The process for preparing aluminum-zinc-magnesium-copper alloy includes: preparing industrial Al powder, Zn powder, Cu powder, and Mg powder by gas atomization method, and obtaining TiB2 / Al-6Zn-3Mg-Cu alloy powder (Zn: 6%, Mg: 3%, Cu: 1%, TiB2: 1%, and the balance being Al) by high-energy ball milling of an appropriate amount of Al powder, Zn powder, Cu powder, Mg powder, and TiB2 nanoparticles. The TiB2 / Al-6Zn-3Mg-Cu alloy powder is placed in a graphite mold, and a cold isostatic pressing machine is used to pre-press at a pressure of 50MPa for 5min. After pre-compaction, powder hot pressing sintering is carried out in a spark plasma sintering furnace to obtain a round pie-shaped sample. The round pie-shaped sample is heated to 450℃ and kept for 1h, and then hot forging, hot extrusion and T6 heat treatment (470℃ / 120min solid solution treatment and 120℃ / 24h aging treatment) are carried out to obtain TiB2 / Al-6Zn-3Mg-Cu aluminum matrix composite rod. The yield strength of the TiB2 / Al-6Zn-3Mg-Cu (Zn: 6%, Mg: 3%, Cu: 1%, TiB2: 1%, and the balance being Al) aluminum matrix composite rod after T6 heat treatment is 495MPa, and the elongation is 10.3%, and the average grain size of TiB2 / Al-6Zn-3Mg-Cu is 1.58μm.
[0043] Compared with the present application, the comparative example 1 adds expensive Ti, B elements (total mass ratio ~ 3%), combined with hot forging, hot extrusion and other complex deformation process, and uses long solid solution + aging heat treatment process (470℃ / 120min solid solution treatment and 120℃ / 24h aging treatment), the obtained TiB2 / Al-6Zn-3Mg-Cu aluminum alloy has a single coarse grain structure, the grain size is 1.58μm, the yield strength is 495MPa, and the elongation is 10.3%. The mechanical properties such as strength and plasticity of the alloy obtained in comparative example 1 are significantly lower than the minimum performance of the alloy obtained in the present application.
[0044] The present application can simultaneously realize grain nanoscale refinement, second phase nanoscale refinement and improve solid solution strengthening effect, simultaneously improve alloy strength, plasticity and hardness; at the same time, a bimodal structure of alternating coarse and fine grains (mainly fine grains, fine grain average diameter ≤558nm, coarse grain average diameter ≤2.6μm, fine grain area ratio ≥55.7%) is obtained, and the solid solution strengthening effect of Mg element in Al matrix is greatly improved (generally ≤1.4wt.% of Mg element in Al matrix by traditional process, ≥5.8wt.% of Mg element in Al matrix by the present application), at the same time, high-density refined Al6(Mn,Fe) (diameter ≤147nm), Mg2Si (diameter ≤131nm) and Al3(Sc,Zr) (diameter ≤4nm) nanoscale strengthening phases are formed. Among them, the ultra-fine nanometer Al3(Sc,Zr) strengthening phase is L12 type, the number density is ≥7.2×10 23 m -3 Compared with the prior art high alloy content, noble metal addition, complex deformation process and high temperature long time heat treatment process, the present application does not add a large amount of noble metal and does not use deformation, high temperature solid solution heat treatment and other complex processes, and reduces the alloy addition cost, simplifies the process, realizes the short process and industrialized production. In addition, the component ratio and process parameters of each embodiment of the present application are different, and the obtained performance is also different, which shows that the present application realizes the best strength and plasticity through the synergistic control of component interaction, element ratio, process and process parameters, at the same time, has high hardness and avoids cracking. The laser additive manufacturing process used in the present application effectively avoids the anisotropy of the material in the additive manufacturing process, which can effectively improve the performance uniformity of the material, and simultaneously improve the strength and plasticity of the material. In addition, only within the process and process parameter range protected by the claims of the present application, can the alloy strength, plasticity and hardness be simultaneously improved.
[0045] In summary, the application obtains the Al-Mg alloy with high strength and high plasticity and high hardness through the synergistic regulation of component interaction, element ratio, process and process parameters. As shown in Table 1, the tensile strength of the Al-Mg alloy after aging is greater than or equal to 598 MPa, the yield strength is greater than or equal to 584 MPa, the elongation is greater than or equal to 11.2%, and the Vickers hardness is greater than or equal to 180 HV.
[0046] Table 1 shows the mechanical properties of the aluminum alloy obtained in all examples and comparative examples
[0047]
Claims
1. A high-strength, high-ductility, high-hardness Al-Mg alloy, characterized in that: The Al-Mg alloy composition, by mass percentage, is: Mg: 5-15%, Mn: 0.4-2.3%, Sc: 0.4-1.5%, Zr: 0.2-1.5%, Si: 0.2-1%, Fe: 0.04-0.2%, with the balance being Al and unavoidable impurities, wherein the impurities are ≤0.02%. Its preparation method includes the following steps: (1) By mass percentage, commercial pure aluminum, Al-20Mn, Al-2Sc, Al-5Zr, Al-20Si and Al-20Fe are melted at 680-800℃, then cooled to 600-750℃, and commercial pure magnesium is added until completely melted. After stirring for 10-60 minutes, an alloy melt is obtained. (2) The alloy melt obtained in step (1) is crushed and solidified by a high-pressure nitrogen atomizer to form metal powder. After screening, Al-Mg alloy powder is obtained, and the particle size of the Al-Mg alloy powder is 5-80μm. (3) After vacuum drying the Al-Mg alloy powder obtained in step (2) at 80-120℃ for 3-8 hours, an aluminum alloy plate is used as the substrate, and 50-600 layers of laser additive manufacturing are performed under high-purity argon protection to obtain an Al-Mg alloy molded part. The laser additive manufacturing process is as follows: the laser scanning is in strip mode, and each layer of laser additive manufacturing requires two laser scanning melting processes. Each laser scanning melting process is as follows: the laser power is 150-420W, the scanning speed is 600-2000mm / s, the powder layer thickness is 20-50μm, and the laser scanning spacing is 100-130μm. Compared with the upper layer of laser additive manufacturing, the scanning path of the lower layer of laser additive manufacturing is deflected counterclockwise by 50-90°, and the additive manufacturing process is performed according to the upper layer process. The density of the Al-Mg alloy molded part is ≥99.7%, and the tensile strength σ b ≥475MPa, yield strength σ 0.2 ≥411MPa, elongation ≥16%; (4) The Al-Mg alloy molded part obtained in step (3) is kept at 300-400℃ for 2-12 hours to obtain a high-strength, high-ductility, and high-hardness Al-Mg alloy; the high-strength, high-ductility, and high-hardness Al-Mg alloy has high-density nanoscale Al6(Mn,Fe) with a diameter ≤147nm; Mg2Si with a diameter ≤131nm; and ultrafine nanoscale Al3(Sc,Zr) reinforcing phase with a diameter ≤4nm. At the same time, a bimodal structure with alternating coarse and fine grains is obtained, with fine grains accounting for the majority, the area of fine grains ≥55.7%, the average diameter of fine grains ≤558nm, and the average diameter of coarse grains ≤2.6μm. The Al3(Sc,Zr) reinforcing phase is of type L12 with a number density ≥7.2×10 23 m -3 The high-strength, high-hardness Al-Mg alloy has a tensile strength σ b ≥598MPa, yield strength σ 0.2 ≥584MPa, elongation ≥11.2%, Vickers hardness ≥180HV.
2. The high-strength, high-ductility, high-hardness Al-Mg alloy according to claim 1, characterized in that: The Al-Mg alloy powder in step (2) has a particle size of 15-53 μm.
3. The high-strength, high-ductility, high-hardness Al-Mg alloy according to claim 1, characterized in that: The aluminum alloy plate mentioned in step (3) is either 5A06 or AA5083.
4. The high-strength, high-ductility, high-hardness Al-Mg alloy according to claim 1, characterized in that: Step (3) describes obtaining Al-Mg alloy molded parts by performing 150-400 layers of laser additive manufacturing under high-purity argon protection.
5. A high-strength, high-ductility, high-hardness Al-Mg alloy according to claim 1, characterized in that: Compared to the upper-layer laser additive manufacturing process, the scanning path of the lower-layer laser additive manufacturing process is deflected counterclockwise by 60-80° in step (3).
Citation Information
Patent Citations
Laser additive manufacturing multi-scale microstructure reinforced eutectic Al-Mg-Si-Cu alloy and preparation method thereof
CN117467875A
Ribbons and powders from high strength corrosion resistant aluminum alloys
US20180010216A1